THE TRADITION OF SUFISM IN THE CONTEXT OF HISTORICAL INTERACTION: THE CASE OF KAZAKHSTAN AND PAKISTAN - Shynar Kanafyeva; Mırzahan Egamberdıyev (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi)
This study examines the tradition of Tasawwuf in Kazakhstan and Pakistan within the framework of historical interactions, offering a comprehensive analysis of its impact on the cultural, social, and religious structures of these countries. Tasawwuf has historically played a pivotal role in shaping the spiritual and societal fabric of Central and South Asia, particularly in Kazakhstan and the South Punjab region of Pakistan. The research evaluates the influence of prominent Sufi orders such as Yasawiyya, Naqshbandiyya, Chishtiyya, and Suhrawardiyya, delving into their roles in religious practices and socio-cultural dynamics. The primary aim of this study is to analyze the reciprocal interactions of these Sufi orders in Kazakhstan and Pakistan, tracing their imprints on religious identity and societal systems. Key topics include the significance of Tasawwuf in the spread of Islam and its influence on religious practices in Central and South Asia; the effects of the Russian Empire’s interventions on Sufi traditions in Kazakhstan, including transformations in practices and shifts in their societal roles; and the contributions of Tasawwuf to political mobilization and social organization in South Punjab. Furthermore, the study explores the Tasawwuf-driven cultural exchanges between Kazakhstan and Pakistan, emphasizing their role in strengthening interregional ties and communication. Employing historical-analytical methods, comparative analysis, and systematic evaluation of primary and secondary sources alongside archival records, the research highlights the social transformations shaped by external pressures, particularly colonization and modernization efforts. Ultimately, this study underscores the role of Tasawwuf as a bridge between the cultures and civilizations of Central and South Asia, demonstrating its profound influence on regional political and social processes beyond its spiritual domain. The findings reveal that Sufi orders not only shaped religious practices but also fortified local cultural resilience against external challenges while fostering new channels of interaction.